Bust a move - Relic, Peter (Citadel Press, Kensington Publishing Corp., 2026)
In 1987, hip-hop was at a tipping point: coastally, commercially, and creatively. New York City ruled the culture, while its hottest record label Def Jam was king. Yet out in LA, a new crew was ready to challenge for the crown, and their fresh spin would upend the industry as the decade reached its peak. Two Los Angeles dance club DJs, Matt Dike and Mike Ross, started their own independent label in Matt's cramped apartment on Santa Monica Boulevard and called it Delicious Vinyl. Hoping to press a few thousand records locally, they signed unknown rappers Tone Loc and Young MC, and after recording "Wild Thing," "Funky Cold Medina," and "Bust a Move," they soon sold nearly ten million copies worldwide. For a fleeting, shining time, aligned with a stunning series of collaborators, Matt Dike was the hottest music producer in the world. Iconic artist Jean-Michael Basquiat, director John Hughes, and the Beastie Boys all entered Matt's inner circle. Then, at the height of his success, Dike disappeared from the scene. Mysteriously, he cut himself loose from his closest friends, colleagues, and family. The life, career, and secrets of "the Howard Hughes of hip-hop" became the stuff of legend. Now, journalist Peter Relic unpacks the truth behind an exhilarating, never-before-told story of the city, the era, and the blazing creativity that changed the landscape of both rap and pop. Filled with unforgettable characters and drawing on dozens of exclusive interviews--including the only in-person sit-down with the enigmatic Matt Dike--Bust a Move is the answer to a mystery, and a celebration of a monumental musical legacy.